Factors influencing trends in trauma-associated orbital cavity reconstruction procedures and time delay: New Zealand national data 2000–2014. (October 2018) - Samaranayaka, Chamil; Samaranayaka, Ari; Barson, Dave; De Silva, RK
Aim: Surgical reconstructions of orbital fractures due to trauma are increasing worldwide. This study identifies characteristics of patients facing such procedures, possible causes for increasing trends, and factors associated with the duration from trauma to surgical procedures. Methods: Trauma-related orbital reconstruction procedures in New Zealand over a 15-year period were identified from Ministry of Health hospital discharge data. Age-standardised rates for each year and age-specific rates for each gender were calculated using age, sex and year-specific population data from New Zealand population censuses. The contribution of these procedures to total trauma-related maxillofacial procedures was assessed. Descriptive statistics were used to identify demographic, trauma-related, and procedure-related characteristics associated with higher frequency and increasing trends. Characteristics independently associated with time delay from trauma to surgery were identified by multivariable Cox regression modelling. Results: Orbital procedures are most common among males and the young to middle aged, and trends in frequency and rates of procedures are sharply increasing outnumbering other types of trauma-related maxillofacial procedures, with interpersonal violence being a major contributor to this increase. Younger age and higher number of injuries are associated with less time delay from injury to procedure while Asian ethnicity, motor vehicle accidents, non-maxillofacial primary diagnoses, and higher number of medical comorbidities are associated with longer delay. Conclusion: The first three findings are consistent with international literature, and could be considered by policy makers when deriving preventive measures. The findings related to time delay are new and could contribute information towards forming clinical guidelines if similar patterns were identified elsewhere.